2013
DOI: 10.2166/wst.2013.779
|View full text |Cite
|
Sign up to set email alerts
|

Improving products of anaerobic sludge digestion by microaeration

Abstract: Biogas, digested sludge and sludge liquor are the main products of anaerobic sludge digestion. Each of the products is influenced significantly by specific conditions of the digestion process. Therefore, any upgrade of the digestion technology must be considered with regard to quality changes in all products. Microaeration is one of the methods used for the improvement of biogas quality. Recently, microaeration has been proved to be a relatively simple and highly efficient biological method of sulfide removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…By comparison of two reactors operating one in anaerobic and another in micro-aerobic conditions, it was found that micro-aeration affects the behavior of anaerobic bacteria consortium. The chemical composition of two anaerobic sludge samples does not differ; however, the micro-aerobic culture showed better dewaterability and low foaming potential and in liquid phase lower concentration of COD of 33% was found (Jenicek et al, 2014).…”
Section: Micro-aerationmentioning
confidence: 83%
“…By comparison of two reactors operating one in anaerobic and another in micro-aerobic conditions, it was found that micro-aeration affects the behavior of anaerobic bacteria consortium. The chemical composition of two anaerobic sludge samples does not differ; however, the micro-aerobic culture showed better dewaterability and low foaming potential and in liquid phase lower concentration of COD of 33% was found (Jenicek et al, 2014).…”
Section: Micro-aerationmentioning
confidence: 83%
“…Additionally, some studies have suggested the possibility of negative effects on biogas yields, due to the deterioration of the methanogenic activity of obligatory microbes necessary for biomethane production [42,87,88]. The possibility of these negative effects was however contradicted in studies presented in [158][159][160]. These contradictory observations suggest that the negative effect on biogas yields may depend on several factors, such as the level of oxygen tolerance by the methanogens present and the nature of the sludge substrate (i.e., granular or flocculent) [42].…”
Section: Desulphurisation Methods a Total Operating Cost (Us $/Y) B Eqmentioning
confidence: 99%
“…42 In addition to the advantages of the microaerobic pretreatment process, substrates with high hydrolysis rate require accurate dosage control to prevent additional VFA accumulation in the system and achieve high methane efficiency. 35,43 Therefore, the need to recognize and use control indicators and criteria of micro-aerobic pre-treatment process is discussed.…”
Section: Effect Of Micro-aerobic Pre-treatment On the Quantity And Comentioning
confidence: 99%